Konstruksi Realitas Sosial pada Cuti Melahirkan untuk Ayah dalam Undang-Undang No. 20 Tahun 2023 - Pascarina, Patrisia Amanda; Hartanto, Louisa Christine; Putri, Ranni Iqlima (Calathu: Jurnal Ilmu Komunikasi, 2024)
Awareness of the role of the father, starting from the process of accompanying his wife giving birth to the process of caring for a newborn baby, has begun to be emphasized in modern society. This awareness then resulted in the Government Regulations Draft (RPP) regarding the management of State Civil Apparatus (ASN) as implementing regulations for Law number 20 of 2023 which will regulate paternity leave rights for male civil servants whose wives are about to give birth. So far, in Indonesia, both government and private institutions only regulate maternity leave for female employees. The social construction that has been formed is that women must take full responsibility in caring for newborn children. This research examines the perceptions of male civil servants and private employees regarding the draft law that will regulate paternity leave. Using Bless and Greifeneder's Social Cognitive Processing, 5 male civil servants and 5 male private employees were invited to participate in the FGD. This research shows that there are still misperceptions among male workers because of their thinking patterns which are still strongly derived from Indonesian patriarchal culture. Even though there are many facts in the form of research results about the role of fathers in childcare, male workers are still dominated by the perception that only women are responsible for childcare. Paternity leave does not need to be long because it can reduce men's productivity in the workplace. In fact, husbands’ presence is not only needed to help the wife in the domestic realm but can also provide emotional support to the wives. All forms of male perception and action are still the result of imitation of habits, customs, and social norms seen and learned in society. Keywords: paternity leave, social construct, FGD, perception, Stuart Hall